The measure of civilization: How social development decides the fate of nations - Morris, Ian. (Unites States of America : Princeton University Press, 2013)
The Measure of Civilization presents a brand-new way of investigating these questions and provides new tools for assessing the long-term growth of societies. Using a groundbreaking numerical index of social development that compares societies in different times and places, award-winning author Ian Morris sets forth a sweeping examination of Eastern and Western development across 15,000 years since the end of the last ice age.
Introduction : quantifying social development -- Methods and assumptions -- Energy capture -- Social organization -- War-making capacity -- Information technology -- Discussion : the limits and potential of measuring development.
Includes bibliographical references and index.
Keywords: SOCIAL HISTORY